(untitled) (Shahroud Journal of Medical Sciences, 2021)
Backgrounds: The study aimed to determine the prevalence and covariates of metabolic syndrome among the elderly residents in nursing homes in Semnan Province, Iran. Methods: This cross-sectional study was conducted among aged participants institutionalized in nursing home in 2018. The study participants’ characteristics were assessed using a demographic assessment form. Moreover, the Mini Nutritional Assessment (MNA) questionnaire, Mentally Assessing Nutritional Assessment (MANA), Katz's Index of Independence in Activity of Daily Living, Mini-Mental State Examination (MMSE) and well-being were applied to assess the participants’ physical and mental status. In addition, Para-clinical and biochemical tests for diagnosis of metabolic syndrome used based on the Adult Treatment Panel (ATPIII). Results: In this study, of 129 eligible participants, 27.7% were suffering from metabolic syndrome. The prevalence of MS in male and female subjects were 26.6% and 28%, respectively. The results of the study indicated a significant relationship between metabolic syndrome and nutritional statues (Pvalue=0.004), mental status (Pvalue=0.001) and ADL (Pvalue=0.003). Moreover, the results showed no significant relationship between well-being and metabolic syndrome. Of all variables of the study, significant relationship between smoking habit, lack of daily activity, abdominal obesity, high systolic and blood pressure, high density lipoprotein cholesterol (HDL-C) HDL-cholesterol, Waist Circumference (WC), systole blood pressure (SBP) were found to be statistically significant. Conclusions: The findings of the study indicated the prevalence of metabolic syndrome among institutionalized elderlies is high. It is recommended to implement preventive and therapeutic measures in this vulnerable group of elderly people. Key words: Metabolic Syndrome, Elderly People, Nursing Homes, Prevalence